Caristi's Fixed Point Theorem in Cone Metric Space. (17th March 2022) - Lael, Fatemeh; Saleem, Naeem; George, Reny
Abstract : In this paper, we provide a short, comprehensive, and brief proof for Caristi-Kirk fixed point result for single and set-valued mappings in cone metric spaces. In addition, we partially addressed an open problem in which Caristi-Kirk fixed point result in cone metric spaces reduces to a classical result in metric spaces and provided a brief justification for a partial positive answer to this open problem using Caristi-Kirk fixed point theorem on uniform space. The proofs given to Caristi-Kirk's result vary and use different techniques.